Older Adults can Learn to Learn New Motor Skills - Seidler, Rachael D. (2007)
Many studies have demonstrated that aging is associated with declines in skill acquisition. In the current study, we tested whether older adults could acquire general, transferable knowledge about skill learning processes. Older adult participants learned five different motor tasks. Two older adult control groups performed the same number of trials, but learned only one task. The experimental group exhibited faster learning than that seen in the control groups. These data demonstrate that older adults can learn to learn new motor skills.